Current problems of the patent tax system - N. Z. Zotikov (Вестник университета, 2021)
The patent system of taxation in the Russian Federation and the conditions for its application have changed several times since 2006. In connection with the abolition of the single imputed income tax from 2021, the relevance of the application of the patent tax system increases. The article analyses the development of the patent tax system, its role in budget revenues, identifies positive and negative aspects, and problematic issues of its application in connection with the changes made since 2021. The authors carried out a comparative study of statistical data on taxation for the city of Moscow and the Chuvash Republic. The paper performed the theoretical calculation of the potential annual income for certain types of economic activity in the conditions of the updated patent taxation system for the city of Moscow and certain regions: the Republic of Tatarstan, the Chuvash Republic and the Republic of Mari El. According to the results of the study, it is concluded that it is advisable to regulate the cost of patents for the subjects of the Russian Federation.